2020
DOI: 10.1080/2162402x.2020.1761176
|View full text |Cite
|
Sign up to set email alerts
|

Blood eosinophilic relative count is prognostic for breast cancer and associated with the presence of tumor at diagnosis and at time of relapse

Abstract: Background: Cancer outcome is associated with circulating immune cells, including eosinophils. Here we analyze the relative eosinophil count (REC) in different breast cancer subtypes. Methods: Stage I-III breast cancer patients were included in the study and classified as REC-high vs low (cutoff 1.5%) or relative lymphocyte count (RLC)-high vs low (cutoff 17.5%). The co-primary endpoints were the breast cancer-specific survival (BCSS) or the time to treatment failure (TTF) in the REC groups. Results: Overall 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 44 publications
(76 reference statements)
3
25
0
Order By: Relevance
“…Evidence indicates the presence of eosinophils in the TME of several human hematological and solid tumors, including BC, even if the mechanisms responsible of the eosinophil infiltration into the tumors are not completely known (92)(93)(94). However, some data show that the high-mobility group box 1 protein (HMGB1), IL-1a, and IL-33 potentially trigger eosinophil recruitment (95).…”
Section: Eosinophilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence indicates the presence of eosinophils in the TME of several human hematological and solid tumors, including BC, even if the mechanisms responsible of the eosinophil infiltration into the tumors are not completely known (92)(93)(94). However, some data show that the high-mobility group box 1 protein (HMGB1), IL-1a, and IL-33 potentially trigger eosinophil recruitment (95).…”
Section: Eosinophilsmentioning
confidence: 99%
“…reported that BC patients with eosinophil counts of less than 55/mm 3 had significantly higher risk of recurrent disease than patients who had normal or high levels of eosinophils ( 102 ). Moreover, a study on a cohort of 930 BC patients reported a benefit for relative eosinophil count (REC)-high vs REC-low in BC-specific survival and in time to treatment failure ( 93 ).…”
Section: Major Players In Bc Immune Microenvironmentmentioning
confidence: 99%
“…We observed a positive association between baseline and post-surgery relative eosinophil count (REC) with pCR and survival [ 56 ]. We also studied the prognostic value of circulating eosinophils in a larger cohort of 930 early-stage breast cancer patients, observing a positive association between higher REC and better outcome, independent of the subtype [ 73 ]. In the subgroup analysis, a better prognosis for almost all subgroups was observed, in particular for patients not receiving chemotherapy or anti-HER2 treatment [ 73 ].…”
Section: Eosinophils and Breast Cancermentioning
confidence: 99%
“…Similar results could be found in recent studies. Low blood eosinophilic relative count was associated with a worse prognosis in 930 breast cancer patients [ 37 ]. Moreover, there was a positive correlation between eosinophilic relative counts and both pathological complete remission and survival rate in triple-negative and hormone receptor-negative/HER2-positive breast cancer patients [ 38 ].…”
Section: Discussionmentioning
confidence: 99%